IMPROVING METHODS OF CHILDREN'S SPEECH DEVELOPMENT THROUGH MUSICAL DIDACTIC GAMES - Eshmurodova Durdona O‘ktamovna (American Journals, 2025)
This article describes the improvement of methods for developing children’s speech through musical didactic games. In the process of knowing the world around him, the child seeks to enter into direct contact with existence. It is extremely important to direct this aspiration in the form of a game, that is, the effectiveness of educational work in preschool institutions largely depends on the ability to organize children's play activities in a purposeful manner.
Keywords: Education, music, didactic games, aesthetics, coherence, pedagogy, creative and regular games, research, cognitive, method, discrimination, creative, innovation, technology, dynamic and interactive, song, poem, rhyme, phonological, skills, empathy.